2000
DOI: 10.1590/s0100-879x2000001100005
|View full text |Cite
|
Sign up to set email alerts
|

Two related thrombin-like enzymes present in Bothrops atrox venom

Abstract: This article describes the presence of two new forms of a thrombinlike enzyme, both with apparent molecular masses of 38 kDa, in Bothrops atrox venom. Both share the ability to cleave fibrinogen into fibrin and to digest casein. Both present identical K m on the substrate BApNA. Their N-terminal amino acid sequences are identical for 26 residues, sharing 80% homology with batroxobin and flavoxobin. Two groups of monoclonal antibodies (mAbs) raised against the purified enzyme forms recognized different epitopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
1
19
0
9
Order By: Relevance
“…Since then, several SVTLEs were described in the literature not only in the same species, such as A. caliginosus [11], A. c. contortrix [12], A. halys blomhoffii [13], A. h. pallas [14,15], B. atrox [16,17], B. jararaca [18], B. jararacussu [19], T. stejnegeri [20] and T. flavoviridis [21 -23], but also in different species, e. g. A. halys [24], A. h. brevicaudus stejneger [25], A. h. ussuriensis [26,27], A. 844 H. C. Castro et al Snake venom thrombin-like enzymes saxatilis [28], B. alternatus [29], B. lanceolatus [30], T. mucrosquamatus [31], T. elegans [32,33], T. jerdonii [34,35], T. stejnegeri [36] and different genus Gloydius (G. ussuriensis and G. shedaoensis) [37,38].…”
Section: Svtle Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several SVTLEs were described in the literature not only in the same species, such as A. caliginosus [11], A. c. contortrix [12], A. halys blomhoffii [13], A. h. pallas [14,15], B. atrox [16,17], B. jararaca [18], B. jararacussu [19], T. stejnegeri [20] and T. flavoviridis [21 -23], but also in different species, e. g. A. halys [24], A. h. brevicaudus stejneger [25], A. h. ussuriensis [26,27], A. 844 H. C. Castro et al Snake venom thrombin-like enzymes saxatilis [28], B. alternatus [29], B. lanceolatus [30], T. mucrosquamatus [31], T. elegans [32,33], T. jerdonii [34,35], T. stejnegeri [36] and different genus Gloydius (G. ussuriensis and G. shedaoensis) [37,38].…”
Section: Svtle Distributionmentioning
confidence: 99%
“…Included in these activities, several SVTLEs have kininreleasing activity, leading to a hypotensive effect [2,63,106]. Generally, the kinin that is released from plasma kininogens by most snake venom enzymes, such as halystase from A. halys blomhoffii [17], flavovilase from Trimeresurus flavoviridis [21] and KN-BJ from B. jararaca venom [107], is bradykinin. Curiously, elegaxobin II from Trimeresurus elegans venom is the unique SVTLE cited so far that is able to release Lys-bradykinin from plasma kininogens [33].…”
Section: Biological Properties Of Svtlementioning
confidence: 99%
“…TLBbar showed of 0.35 nmoles/min on BApNA substrate (Figure 4(a)), with Michaelis-Menten kinetic behavior (Figure 4(c)) and max and of 0.42 nmol/min and 0.433 mM, respectively (Figure 4(d)); these values are similar to other thrombin-like snake venom, as TLE-1 and TLE-2 isolated from B. atrox ( 0.33 mM and 0.46 mM, resp.) [37] and thrombin-like from Lachesis muta muta ( of 0.075 mM and max of 0.36 nmol/min) [38]. These results suggested that the catalytic mechanism of this enzyme is probably involved in an active site organization similar to that of trypsin.…”
Section: Discussionmentioning
confidence: 83%
“…Caso 1 indicam incoagulabilidade sanguínea [20]. Uma fração do veneno é composta pelas serinoproteases, enzimas com atividades do tipo trombina [9], que são responsáveis por hidrolisar o fibrinogênio em fibrina, ativando os fatores II e V da cascata de coagulação e levando à formação da trombina exógena [25]. O aumento do tempo de protrombina e do tempo de tromboplastina parcial ativada observados no Caso 1 2 , e a normalidade desses testes no Caso 2, somado ao fato dos dois casos terem ocorrido no mesmo ambiente e dia, provavelmente pelo mesmo indivíduo, justifica a maior gravidade do Caso 1 2 , culminando com óbito.…”
Section: Caso 1unclassified